Decompositions of fuzzy *g-continuity - M.Vidhya Priyac; O. Ravi (Journal of New Results in Science)
of a weaker form of fuzzy continuity, namely fuzzy *g-continuity,by providing the concepts of fuzzy *gt-sets, fuzzy *gα∗-sets, fuzzy*gt-continuity and fuzzy *gα∗-continuity